Skogseldens påverkan på epifytiska trädlavar på tall i relation till brandintensiteten - Jonsson, Teresa (2006)
Not much is today known about how epiphytic lichens are effected by fire. A considerable part of the fires in Sweden today are prescribed fires for the purpose of environmental conservation. How these fires affect lichens is largely unknown. The aim of this study is to find out how epiphytic fruticose and foliose lichens on Scots pine are affected by fire, and to elucidate the relationship between fire intensity and the survival of lichens and later re-colonization. The study was performed at three locations just outside Umeå in Västerbotten that were burned 5-7 years earlier. In all locations there were larger groups of surviving Scots pines with varying amount of fire-damage in the crown, which enabled a reconstruction of fire intensity. A total of 36 pine-trees were selected with a large variation in the height of the soot and the height of the lowest surviving needles in the crown. The sample trees were examined on the windward side and the leeward side of the trunk along a 10 cm wide strip up to approximately 4 metres. The height of the char and new lichen colonisation on the char, as well as the size and species of each of the surviving lichens above the char was noted within the 10 cm strip. Also the uppermost height of the cork bark, the height of the tree, circumference, and scorch height (lowermost living needles in the crown) was recorded. A total of 12 unburned control trees were examined in adjacent stands. In many cases, the lowest surviving lichen was found as close as 10-20 cm above the char on the pine trunks. There was a positive linear relation between the height of the lowest surviving lichen and both the height of the surviving needles in the crown and the height of the soot. The lowest surviving needles were always considerably higher up than the lowest surviving lichen, which indicates that the lichens can tolerate a considerably higher temperature than pine needles. On the most damaged pines, with a scorch height of 10-13 m, the height of the lowest surviving lichens on the windward side and leeward side was 2 and 4 m respectively. The unburned control trees had the greatest lichen coverage (20-30%) in the height interval 0,5-1 m above ground and rapidly diminishing along the trunk. In the height interval 3-3,5 m, the coverage was already less than 2%. The lichen flora was dominated by Hypogymnia spp. on both control trees and burned trees. All the recorded lichen species are commonly occurring in Sweden. The new colonisation on the charred bark was effective, with a clear dominance of Hypogymnia spp. The most frequent new colonisation occurred at the base of the trunk, and was richest on the leeward side of the trunk, probably a consequence of the greater charring of the bark there. The results clearly show that epiphytic lichens can stand a higher temperature than pine needles, but that the lichen populations on pines could be seriously affected by fire, since they are concentrated to the lower part of the trunk, which is covered by cork bark. Yet the re-colonisation was effective already a few years after fire for the observed species. The relationship between fire intensity and height of mortality is probably of a general nature, and can hint at the survival possibility also for more rare lichen species in wildfires or management fires.